ЗАСТОСУВАННЯ ВПРАВ ТРЕНІНГУ НАВЧАЛЬНОГО ДІАЛОГУ В ШКІЛЬНОМУ КУРСІ ЕКОНОМІЧНОЇ І СОЦІАЛЬНОЇ ГЕОГРАФІЇ УКРАЇНИ (Педагогіка вищої та середньої школи, 2003)
O.L. Tkachenko. Postgraduate of the Chair o f Pedagogical Creativity, Sumy State Pedagogical University.The use of exercises o f educational dialogue in the school course of ,,Economic and social geography o f Ukraine”.For the purpose of providing with conditions of harmonious development of a pupil s personality in educational establishments of general education we have developed a set of exercises of educational dialogue. The use of the exercises, which are adopted to the course of  ,,Economic and Social Geography o f Ukraine (9th form)”, is analyzed in the theses. Examples are given.